Production of eco friendly DME fuel over sonochemically synthesized UiO66 catalyst - Mahdi Sharifi; Rouein Halladj; Sima Askari (Scientific Reports, 2024)
Abstract The ultrasound-assisted preparation of UiO-66 was carried out at T = 80–220 °C, and the catalytic performances were evaluated in methanol conversion. Also, physicochemical properties were assessed by XRD, SEM, PSD, FTIR, N2 adsorption–desorption, TG-DTG, and NH3-TPD analysis. The characterization proved that increasing the synthesis temperature positively affected the crystallinity, specific surface area, thermal stability, and acidity of the catalysts. Besides, the catalysts' performance was investigated in the methanol conversion reaction (T = 350–450 °C, P = 1 atm, and WHSV = 5 h−1), leading to the DME (Dimethyl Ether) production. Rising reaction temperature increased the methanol conversion and DME yield. The synthesized sample at 220 °C had the best properties and performance with conversion and yield of about 38% and 51%, respectively. The stability test for the UiO-66-220 (University of Oslo 66) catalyst was performed at 450 °C for 12 h, and the activity remained stable for about 5 h. Furthermore, the used catalyst was characterized via XRD and TG analysis.